Bone in heart failure. Issue 2 (22nd February 2020) - Loncar, Goran; Cvetinovic, Natasa; Lainscak, Mitja; Isaković, Andjelka; von Haehling, Stephan
Abstract: There is an increasing interest in osteoporosis and reduced bone mineral density affecting not only post‐menopausal women but also men, particularly with coexisting chronic diseases. Bone status in patients with stable chronic heart failure (HF) has been rarely studied so far. HF and osteoporosis are highly prevalent aging‐related syndromes that exact a huge impact on society. Both disorders are common causes of loss of function and independence, and of prolonged hospitalizations, presenting a heavy burden on the health care system. The most devastating complication of osteoporosis is hip fracture, which is associated with high mortality risk and among those who survive, leads to a loss of function and independence often necessitating admission to long‐term care. Current HF guidelines do not suggest screening methods or patient education in terms of osteoporosis or osteoporotic fracture. This review may serve as a solid base to discuss the need for bone health evaluation in HF patients.